Advances in Acute Migraine Therapy: Triptans Compared with CGRP Receptor Antagonists - Chodor, Michał; Kryś, Zuzanna; Michalik , Zuzanna (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Migraine is one of the most common and disabling neurological disorders. Attacks significantly decrease quality of life and daily functioning; therefore, effective treatment is crucial. Triptans have remained the standard therapy for many years, while calcitonin gene-related peptide (CGRP) receptor antagonists (gepants) represent an alternative. The aim of this review is to compare their effectiveness and safety. Materials and Methods: This review evaluates the efficacy and safety of acute migraine therapies, focusing on triptans and gepants. Literature was searched in PubMed/MEDLINE, Scopus, and Google Scholar. State of Knowledge: Both therapies are effective in treating migraine pain and associated symptoms. Triptans act as selective 5-HT₁B/₁D receptor agonists with rapid onset. However, their vasoconstrictive effects limit use in patients with cardiovascular disease. Gepants inhibit the CGRP pathway and do not cause vasoconstriction, suggesting a better safety profile, although with a slower onset. Summary: Triptans remain first-line therapy, while gepants are a suitable alternative. Individualized treatment is essential.